ESPEN guidelines on definitions and terminology of clinical nutrition. Issue 1 (February 2017) - Cederholm, T.; Barazzoni, R.; Austin, P.; Ballmer, P.; Biolo, G.; Bischoff, S.C.; Compher, C.; Correia, I.; Higashiguchi, T.; Holst, M.; Jensen, G.L.; Malone, A.; et al.
Summary: Background: A lack of agreement on definitions and terminology used for nutrition-related concepts and procedures limits the development of clinical nutrition practice and research. Objective: This initiative aimed to reach a consensus for terminology for core nutritional concepts and procedures. Methods: The European Society of Clinical Nutrition and Metabolism (ESPEN) appointed a consensus group of clinical scientists to perform a modified Delphi process that encompassed e-mail communication, face-to-face meetings, in-group ballots and an electronic ESPEN membership Delphi round. Results: Five key areas related to clinical nutrition were identified: concepts; procedures; organisation; delivery; and products. One core concept of clinical nutrition is malnutrition/undernutrition, which includes disease-related malnutrition (DRM) with (eq. cachexia) and without inflammation, and malnutrition/undernutrition without disease, e.g. hunger-related malnutrition. Over-nutrition (overweight and obesity) is another core concept. Sarcopenia and frailty were agreed to be separate conditions often associated with malnutrition. Examples of nutritional procedures identified include screening for subjects at nutritional risk followed by a complete nutritional assessment. Hospital and care facility catering are the basic organizational forms for providing nutrition. Oral nutritional supplementation is the preferred way of nutrition therapy but if inadequate then other forms of medical nutrition therapy, i.e. enteral tube feeding and parenteral (intravenous) nutrition, becomes the major way of nutrient delivery. Conclusion: An agreement of basic nutritional terminology to be used in clinical practice, research, and the ESPEN guideline developments has been established. This terminology consensus may help to support future global consensus efforts and updates of classification systems such as the International Classification of Disease (ICD). The continuous growth of knowledge in all areas addressed in this statement will provide the foundation for future revisions.